ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN NASABAH MEMIIH JASA PERBANKAN Studi Kasus pada PT. BRI (Persero) Tbk UNIT BULU-BULU MAROS - Mashur Razak; Khaerullah H Khaerullah H (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aimed to analyze the influence of Cultural Affairs, Reference Group And Attitude Formation Against customer choose Banking Services at BRI feathers. Samples were taken of 100 respondents. The indicators in this study is a social culture, reference group, attitude formation. Y variables were analyzed with SPSS. These results indicate that the socio-cultural variables (X1), a reference group (X2) and the formation of attitudes (X3) partially and simultaneously and significant positive effect on customer decision in choosing banking services is a social culture